Time budget pressure on audit quality with audit structure, independence, and audit supervision as moderating variable - Jati , I Ketut; Suprasto , Herkulanus Bambang (International research journal of management, IT and social sciences, 2020)
The audit quality of the public accounting firm / KAP was questioned as there were several cases of fraud, irregularity, and other unhealthy accounting practices that linked several public companies that had been audited and obtained an unqualified opinion / WTP. Empirical research shows that time budget pressure has an effect on audit quality but is not linear because moderating factors are suspected, including time budget pressure, audit structure, independence, and audit supervision. The purpose of this study was to determine the effect of time budget pressure on audit quality. The population of KAP auditors in Bali Province and the research sample was determined by purposive sampling method. The data collected were tabulated and analyzed using the Moderated Regression Analysis (MRA) technique through the following stages: classical assumption test, model feasibility test (F test), determination coefficient analysis (Ajd. R2), research hypothesis testing (t-test) for both partial and moderating effect. The results of the research show that time budget pressure has a negative effect but not statistically significant on audit quality. Furthermore, audit structure, independence, audit supervision attenuate the negative effects of time budget pressure on audit quality.